A reference architecture for application marketplace service based on SaaS. (1st January 2011) - Chang, Shih-Fang
Constructing application marketplace to supply application services is a new trend of service industry. However, traditional techniques used to build a marketplace may not be easy to cooperate and integrate. The construction process also wastes huge cost and time. Therefore, the valuable reference architecture for easy building the application marketplace becomes more important. This research proposed the reference architecture for a new marketplace service construction and integration. The proposed system is named AMaaS (Application Marketplace as a Service), which redesigned the original architecture of online application marketplace according to the concept of Software as a Service (SaaS). Besides, this work preserves the feasible features to conjunct with other optional functionalities, like payment service and certification service, etc. Our proposed system is the state-of-the-art towards to develop the internet integrated service for mobile devices and applications.